STRATEGY FRAMEWORK DEVELOPMENT BASED ON BUSINESS COMMERCIAL INTEGRATING CO-CREATION PROCESS TO GUIDE PSS TRANSITION - Kusumaningdyah, Widha; Himawan, Rakhmat; Ardianwiliandri, Raditya (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2023)
Product-Service System (PSS) is considered as a promising solution for manufacturing industry to address environmental and economic issues simultaneously. Despite the potential benefit, PSS uptake across industries is hardly found. This research aims to draw current state of manufacturing industry upon theoretical framework of PSS typology to get insights of the gap in between. The study exhibits PSS level assessment indicated by key character identified from the various literature of PSS typology. The study also introduces co-creation process as a strategy to increase system capability within PSS framework. Manufacturing companies are selected from various source of literature and article in PSS discussion to exercise PSS assessment. The evaluation of PSS current practice reveals that commercial based transaction (B2B and B2C) play a significant role to determine the suitable development strategy for PSS transition. Furthermore, the type of business commercial also determines the customer involvement level in co-creation process. A framework to guide PSS transition based on the business commercial is established, comprehends the type of value proposition, suitable business strategy, network configuration, and co-creation level.